Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, dan Inflasi terhadap Kemiskinan di Kota Banjarmasin Tahun 2007-2018 - Ellisa Dewi Norsita Fahjarini; Eny Fahraty (PPJP Universitas Lambung Mangkurat, 2020)
This study was conducted to determine: (1) The Effect of economic growth on poverty in Banjarmasin City, (2) The number of population in poverty in Banjarmasin City, (3) the Effect of inflation on poverty in Banjarmasin City.This type of research is quantitative research with the method used that is using multiple linear regression methods. The variables used are poverty, economic growth, population, and inflation. While the data used to analyze this research uses time-series data by using secondary data that are data sources that do not directly provide data to data collectors, such as data from the Central Statistics Agency (CSA) Banjarmasin City.The results showed the variables of economic growth, population, and inflation together affected poverty, and economic growth factors dominantly influenced poverty in the city of Banjarmasin in 2007-2018.